Evaluación de los riesgos laborales en la unidad de mantenimiento y reparación de vehículos livianos y pesados del gobierno autónomo descentralizado de la provincia de Cotopaxi 2015. propuesta procedimientos de trabajo seguro - Toapanta Toapanta, Luis Alexis (2016)
The research work is focused on industrial safety and occupational health at the " Maintenance and Repair of Light and Heavy Vehicles Autonomous Government Decentralized Cotopaxi Province Unit" the problem with the institution are the high rates of accidents and labor incidents, occupational hazards these effects are caused by the lack safety management and occupational health as all members of the institution have as reactive culture, is that decision after it has passed an unexpected event are taken. Regarding the methodology several investigations were applied: field descriptive, the application of these have gotten information concerning the asked question, which was conducted by the survey, and the risk matrix was made with technical standard prevention (GTC-45)….